Agreement of Digital Panoramic Radiographs with and without Software Enhancement in the Diagnosis of roximal Dental Caries in Primary Molars - Somayeh Nemati; Seyedeh Tahereh Mohtavipour; Seyedeh Saeede Mohtavipour; Naghmeh Abdollahi (Mashhad University of Medical Sciences, 2019)
Introduction: Dental caries is the most common chronic condition in children. Recently, there has been a growing tendency to using digital panoramic radiography among clinicians. The present study aimed to determine the accuracy of digital panoramic radiography with and without software enhancement in the diagnosis of proximal dental caries in primary molars. Methods: This study was conducted using 27 digital bitewings and panoramic radiography in 2016. Initially, panoramic radiography without enhancement was observed by a maxillofacial radiologist. Afterwards, sharpen, pseudocolor, emboss, and reverse-contrast enhancements were applied, and radiography was re-evaluated. In addition, bitewing radiography was investigated. After data collection, data analysis was performed in SPSS using the Kruskal-Wallis test and kappa coefficient agreement at 95% confidence interval. Results: No significant difference was observed between digital panoramic and bitewing radiography in the diagnosis of interproximal caries in primary molars. The maximum coefficient of agreement was obtained in maxillary and mandibular E (ƙ=0.893) and maxillary and mandibular D (ƙ=0.874 and ƙ=0.897, respectively). Moreover, no significant differences were denoted between the enhancement tools in the diagnosis of interproximal caries (P>0.05). In general, sharpen four was found to be the most powerful tool in this regard. Conclusion: According to the results, digital panoramic imaging system was as accurate as bitewing radiography in the diagnosis of proximal dental caries. However, using enhancement tools in panoramic radiography was not helpful in the diagnosis of caries.